Sedimentology of Pleistocene Outwash and Glaciolacustrine Deposits in East-central Wisconsin - Czech, Carrie (UWM Digital Commons, 2016)
The Green Bay Lobe was one of several lobes of the Laurentide Ice Sheet (LIS) to enter Wisconsin during the recent Wisconsinan glaciation. Kewaunee Formation deposits in the Tower Hill sand and gravel pit near the city of De Pere in east-central Wisconsin were previously interpreted to be the result of an ice-contact delta, prograding into former glacial Lake Oshkosh (Mickelson and Mode, 2007). Estimates of water depth in the lake had been poorly constrained as they had been estimated by the elevation of the outlet channels and a few scattered, poorly-preserved strandline deposits (Hooyer, 2007). Reexamination of these Kewaunee Formation deposits suggests they were part of a grounding-line fan system prograding into glacial Lake Oshkosh, that glacial Lake Oshkosh was an ice-contact lake with a dynamic ice front, and that lake levels changed throughout time. The occurrence of wave ripples found as basal deposits in most sections suggests that water depth, although not measurable, was relatively shallow with at least one large draining event. Thrust sheets in silt, superimposed styles of different types of folding, and different orientations of sediment rafts, nappe-like structures, and/or sheath(-like) folds suggests deformation that occurred in the northwest corner of the pit was by ice shove with a nearby ice margin (Mills and Wells, 1974). By addressing the aforementioned topics, the ice dynamics (i.e., ice recession and readvance history) of the Green Bay Lobe during deposition of the Kewaunee Formation has been more fully resolved.